Interferensi Morfologis Pada Catatan Buku Harian Siswa Kelas VII Semester I SMP Muhammadiyah 8 Surakarta Tahun Ajaran 2015/2016 - Nianti, Nianti; , Prof. Dr. Abdul Ngalim M.M (2016)
The purpose of this study is describes the types and causes of the morphological interference in the diary seventh grader students of the first semester of SMP Muhammadiyah 8 Surakarta academic year 2015/2016. Type of research is a qualitative research. Data collection techniques used in this study is documentation techniques. Analysis of the data in this study using intralingual match. It can be concluded that the interference morphological types include: (a) affixation classified into three kinds: prefixes, suffixes, and konfiks, (b) reduplications classified into two kinds: the repetition of the whole on the basic shape and repetition of a basic shape with a particle. Factors that cause interference morphology include: (a) bilingualism students in daily communication both with family, teachers and friends of the school, (b) entrainment mother tongue in everyday life, and (c) the disappearance of the words that are rarely used.